The Influence of Leadership and Communication on Outsourced Employee Performance - Mulyadi, Dede; Hasbi, Hariandy (Dinasti Publisher, 2025)
This study aims to analyze the influence of leadership and communication on the performance of outsourcing employees at PT X. The research background highlights the crucial role of effective leadership and clear organisational communication within outsourcing. This research employs a quantitative method with a descriptive, associative and verificative approach. The population consists of 140 employees, of whom 104 respondents were selected using purposive sampling. Data were collected through questionnaires and the analysis was conducted using multiple linear regression. The findings reveal that leadership has a positive and significant effect on employee performance. And also communication. Simultaneously, both variables contribute significantly to the performance of outsourcing employees at PT X. These results indicate that the synergy between effective leadership and well-structured communication enhances productivity and overall work quality. The study provides valuable insights for PT X's management in formulating more effective human resource development strategies.